Understanding the concept of Anupana (vehicle): A Review - Goyal, Anushka; Joshi, Shruti; Yadav, Chhaju Ram (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is regarded as the science of life. It is famous all over the world because of its unique concepts. Concept of Anupana(Vehicle) being one of them. It can be termed as fluid vehicle which are consumed along with or after intake of medicine or food. It enhances the action of Dravya that is run within the body. If Anupana(Vehicle): is given with food, it helps in digestion and provide nourishment to body. On the other hand, if it is taken after or with medicine, it makes medicine palatable and helps to carry medicine to target site and also reduce the adverse effects of that particular drug. It assists the action of those medicines in their actions and it is decided in accordance to Srotas (channels), disease, Dosha concerned, properties and consistency of the medication. Best Anupana(Vehicle) is Antariksha jala (rain water) and Madhu(honey). An effort has been made to review about understanding the concept of Anupana(Vehicle) in detail.